2002
DOI: 10.1152/ajprenal.00199.2002
|View full text |Cite
|
Sign up to set email alerts
|

Overload proteinuria is followed by salt-sensitive hypertension caused by renal infiltration of immune cells

Abstract: Recent evidence suggests that salt-sensitive hypertension develops as a consequence of renal infiltration with immunocompetent cells. We investigated whether proteinuria, which is known to induce interstitial nephritis, causes salt-sensitive hypertension. Female Lewis rats received 2 g of BSA intraperitoneally daily for 2 wk. After protein overload (PO), 6 wk of a high-salt diet induced hypertension [systolic blood pressure (SBP) = 156 +/- 11.8 mmHg], whereas rats that remained on a normal-salt diet and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(143 citation statements)
references
References 47 publications
(81 reference statements)
13
129
0
1
Order By: Relevance
“…Indeed, we have noted a remarkable relationship between the presence of T cells and macrophages in the interstitium with salt-sensitive blood pressure in numerous models. [42][43][44] More importantly, we also found that the reduction of the renal inflammatory response by mycophenolate mofetil could prevent the salt-dependent hypertension that occurs following subcutaneous angiotensin infusion, 42 following the temporary inhibition of nitric oxide synthase 43 and the hypertension that occurs with protein overload nephropathy. 44 Subsequently, a large number of studies from several laboratories, including our own, found that treatments directed to suppress renal inflammation are associated with prevention or amelioration of hypertension.…”
Section: Renal Microvascular Disease and Interstitial Inflammation Armentioning
confidence: 59%
“…Indeed, we have noted a remarkable relationship between the presence of T cells and macrophages in the interstitium with salt-sensitive blood pressure in numerous models. [42][43][44] More importantly, we also found that the reduction of the renal inflammatory response by mycophenolate mofetil could prevent the salt-dependent hypertension that occurs following subcutaneous angiotensin infusion, 42 following the temporary inhibition of nitric oxide synthase 43 and the hypertension that occurs with protein overload nephropathy. 44 Subsequently, a large number of studies from several laboratories, including our own, found that treatments directed to suppress renal inflammation are associated with prevention or amelioration of hypertension.…”
Section: Renal Microvascular Disease and Interstitial Inflammation Armentioning
confidence: 59%
“…Proteinuria was determined in 24-h urines collected at baseline, at 8 wk, and at 12 wk before death. Systolic blood pressure was determined by tail cuff plethysmography (IITC Life Scientific Instruments, Woodland Hills, CA) at baseline and at the end of the experiment as described in previous communications (2,26,33,34). All rats had been preconditioned to the procedure, and at the time when the blood pressure was determined they were allowed to rest in the restrainer for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…10 Several recent studies have provided convincing evidence that the renal proinflammmatory response has an important role in mediating salt-sensitive hypertension. 31,32 In a previous study, quantitative trait locus analysis identified the P2X 7 gene as a candidate gene for hypertension, by using F2 rats derived from DS and LEW rats. 13 In the present study, expression levels of P2X 7 mRNA and protein in the kidneys of DS were much higher than those in the kidneys of LEW with normal diets.…”
Section: P2x 7 Expression Is Higher In the Kidneys Of Ds Ratsmentioning
confidence: 99%